Trends in gallbladder cancer incidence in the high- and low-risk regions of India - Phadke, Prachi Ravindra; Mhatre, Sharayu Sitaram; Budukh, Atul Madhukar; Dikshit, Rajesh Prabhakar (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Gallbladder cancer (GBC), a common cancer surrounding the Gangetic belt of India, accounts for 80%–90% of biliary tract cancers. GBC incidence shows striking geographical variation in India. Materials and Methods: We used the data from the National Cancer Registry Programme for the year 2001–2014 to study the time trends of GBC in the high- and low-risk geographical regions of India. Annual percentage change (APC) in age-adjusted incidence rates was computed by log-linear regression model. Results: Among females, a statistically significant increase in trend was observed in Cachar (APC: 7.0, P = 0.02), Delhi (APC: 4.0, P = 0.04), and Kamrup (APC: 4.3, P = 0.02) marked under high-risk region and in Bengaluru (APC: 5.7, P = 0.04) and Pune (APC: 3.4, P = 0.04) marked under low-risk region. Among males, increasing but statistically nonsignificant trends were observed in Cachar, Dibrugarh, Kamrup, Nagpur, and Sikkim, whereas decreasing trends were observed in Bengaluru, Barshi, Bhopal, and Kolkata. Aurangabad showed a statistically significant decrease in trend (APC: −14.5, P < 0.001) among males. Conclusion: The time trend and pattern of GBC have striking differences within the country as well as in state. Further large-scale region-wise studies are needed to find the risk factors of GBC.
Keywords: Gallbladder cancer; incidence rate; India; trend